Qualitative Evaluation on the Use of Pneumonia Antibiotics for Covid-19 Patients at X Hospital Bali in 2020 - Wirda Anggraini; Fitria Rahma Fauzia; Arief Suryadinata; Burhan Ma'arif; Ni Nyoman Sri Budayanti; Fransiska Rosari Dewi (Borneo Journal of Pharmacy, 2023)
Coronavirus disease-19 (Covid-19) is a pandemic that has caused various complications, including pneumonia. One of the therapies used in Covid-19 with pneumonia complications is antibiotics. Antibiotics must be used appropriately to prevent antibiotic resistance. A method to reduce the number of antibiotic resistances is evaluating the use of antibiotics qualitatively using the Gyssens method. Therefore, this study aims to describe the profile and rationality of using pneumonia antibiotics for adult Covid-19 patients at X Hospital from January to December 2020. The data was collected retrospectively on adult patients using the patient's medical record data, and the sample was determined using the purposive sampling technique. There were 117 samples of medical record data processed in this study. This study concluded that the use of antibiotics for patients with Covid-19 disease consisted of single antibiotic usage, i.e., azithromycin in 82 cases (70.09%), and levofloxacin in 30 cases (25.64%), and switched antibiotics usage, i.e., azithromycin to levofloxacin in 5 cases (4.27%). The rationality of using antibiotics using the Gyssens methods was 90.60% with rational or appropriate antibiotics use (category 0). Moreover, there was 9.40% irrational drug use (category I-VI), comprising antibiotics for a longer time than it should be, in 11 cases.